Measure what you treasure! - A maternity dashboard - Joanna Jyothsna; Prema D' Cunha; Chethana Bolanthakodi (Wolters Kluwer Medknow Publications, 2020)
Background: Clinical quality dashboards equip hospitals with a simple method for maintaining and monitoring clinical quality indicators. The maternity dashboard. provides an opportunity to integrate managerial, organizational, and clinical audits to improve quality of care. It has four broad categories: clinical activity, workforce, clinical outcome, and complaints/risk incidents. It can be used to benchmark activity and monitor performance against the standards agreed locally for the maternity unit on a monthly basis. Aim: The aim of this study was to design and implement a maternity dashboard to improve maternal and child health care. Settings and Design: This was a retrospective observational study conducted at a tertiary care hospital. Materials and Methods: Data were collected manually from outpatient department, labor ward, neonatal intensive care unit registers, and electronic records from June 2018 to May 2019 in a tertiary care hospital. Goals for each of the parameters were set, as well as upper and lower thresholds, and the data were analyzed. A suggested approach is to use the traffic light system, such as "green," "amber," and "red." All the parameters after analyzing were noted on the dashboard. Results: During the study period of 1 year, there were 3750 deliveries. Auditing was done for various clinical activity indicators along with clinical outcome (both maternal and neonatal) and triaged using traffic light colors on a monthly basis. Conclusions: Maternity dashboard facilitates targeted quality improvement initiatives. They help in comparing current performance against expected standards and hence helpful in driving changes toward optimum maternal and child health.